Rapid spectroscopic method to assess moisture content in free and packaged oregano (Origanum vulgare L.) - Mendes Novo, Johanna (2016)
A spectroscopic study on oregano has been performed in order to find optical parameters that could be related to moisture content. Reflectance spectra have been obtained varying excitation wavelengths from the visible to the near infrared (NIR) regions of the electromagnetic spectrum. The latter region was very sensitive to water content displaying good correlations between reflectance values and moisture. Reflectance measurements were also performed by interposing a film of a commercial packing material (composed of polyethylene terephthalate and polyethylene) between the excitation source and the oregano sample. We managed to infer the moisture content of the samples through the packaging from the measurement of the diffuse reflected light. The results show the applicability of this spectroscopic technique to the non-destructive sensing of moisture for free or packaged oregano, whenever the wrapping film does not show absorption at 1440 or 1920 nm.